Characterization of Minerals, Metals, and Materials 2020 - Li, Jian (Materials scientist) (Minerals, Metals & Materials Series,, 2020)
This collection gives broad and up-to-date results in the research and development of materials characterization and processing. Topics covered include advanced characterization methods, minerals, mechanical properties, coatings, polymers and composites, corrosion, welding, magnetic materials, and electronic materials. The book explores scientific processes to characterize materials using modern technologies, and focuses on the interrelationships and interdependence among processing, structure, properties, and performance of materials.